A Comparative Study of Vitamin D Level and Lactate Dehydrogenase Activity in Relation to Oxidative Stress in Women with Osteoporosis - Abdlkarem, Husham A.; Zainulabdeen, Jwan A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Osteoporosis (OP) is a silent disease that affects the microarchitecture of the skeleton bones, leading to a drop in mineral levels and an increase in fracture rates. This condition is more common in women than men, especially postmenopausal women, due to decreased production of estrogen, a hormone that regulates bone formation and bone resorption. Oxidative stress is a known factor in the development of OP, resulting from an imbalance in the production of oxidants and antioxidants. Hip and arm fractures are particularly common in women with OP. Objective: The study aimed to evaluate the activity of Lactate Dehydrogenase (LDH) and oxidative stress (OS) levels in postmenopausal women with osteoporosis and varying levels of vitamin D, and to compare these groups based on the measured parameters. Subjects and Methods: This study was conducted at the Baquba Teaching Hospital in Diyala, Iraq, from October 2022 to January 2023. The study involved 100 women whom were divided into two groups, 50 with normal vitamin D levels and 50 with abnormal vitamin D levels. The malondialdehyde (MDA) level was evaluated using the Satoh-modified approach. Results: According to the statistical analysis conducted with the SPSS program, there was a significant difference (P<0.001) in Vitamin D levels between the groups (OPn. D) and (OPab.D). Additionally, significant increases were observed in LDH activity (P<0.001) and MDA levels (P<0.05) for the group (OPab.D) in comparison to (OPn. D). Conclusion: The current study has indicated that women suffering from osteoporosis (OP) have higher levels of LDH and MDA. Additionally, there is an inverse correlation between vitamin D and these two variables; this correlation suggests that vitamin D may possess antioxidant properties that reduce the effects of oxidative stress (OS) in the body. Therefore, vitamin D may help in reducing LDH levels.